PENERAPAN MANAJEMEN PROGRAM ODF DI PUSKESMAS SIDOARJO KABUPATEN SIDOARJO TAHUN 2019 - Aisyah Putri Tauladani; Hadi Suryono; Setiawan . (Poltekkes Kemenkes Surabaya, 2020)
Abstract : Management is a process that consists of planning, organizing, implementing, and supervising to achieve goals or objectives effectively in achieving through the implementation of well-implemented and correct and quality, based on the results of situation analysis supported by accurate and efficient data and information as utilize available resources. This study aims to determine the implementation of ODF program management carried out by Puskesmas in order to achieve performance targets in improving the program. This research is a descriptive study with a cross sectional approach. The object of research is the management of the implementation of environmental health programs for villages that have not yet ODF. The subjects of this study were respondents consisting of leaders of the Puskesmas, environmental health workers and other personnel involved in managing environmental health. Data collection techniques were carried out by questionnaires and interviews. The results of the Sidoarjo Community Health Center have been good at implementing the ODF program. The results of the ODF program management function for observation got a value of 85.4% and the interviewee scored 72.5%. The results of recapitulation based on economic level in two villages received a score of 59.09% and 48.03%, for the education level in two villages the scores were 36% and 43%, the level of knowledge of the two villages was 56% and 41%. In conclusion, the results of management at the puskesmas get good results and the results from the community get quite good results. It is recommended for the community to find information about STBM and cooperate with village facilitators and the government.Keywords : Management, ODF Program